Effect of Various Concentrations of Sulphur Dioxide Pollution on Chlorophyll Pigment of Pisum sativum L. (PEA) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
More significant are the impacts of SO2 pollution on biochemical and agronomic processes. A lot of people in India and other nations rely on peas (Matar) as a protein source. Sulphur dioxide has a negative effect on pea plant species, causing a decrease in their total biochemical pigments. The present investigation examined the effects of different concentrations of sulphur dioxide on the chlorophyll content of pea plant leaves found reduction in chlorophyll content- chl-a, chl-b at higher concentration of sulphur dioxide.